Pemeliharaan Larva Ikan Kerapu Sunu (Plectropomus Leopardus) Stadia Awal Pada Bak Berbeda Warna - Setiawati, Ni Ketut Maha; Melianawati, Regina (Journal of Marine and Aquatic Sciences; Vol 6 No 1 (2020)DO - 10.24843/jmas.2020.v06.i01.p04, 2020)
Tank color supposed to have influence to larvae rearing of fish. The aim of this research was to know the effect of different tank colors in early stage larvae rearing of coral trout that started from hatching until 10 days after hatching. The tank colors tested were Yellow (Y), Blue (B), White (W) and Black (Bc). Larvae were fed rotifers and copepods. The observed parameters were rearing success rate, survival rate, total length, number of rotifers in larval digestive tract and light intensity above the water surface and which is reflected from the water. The results showed, rearing success rate in treatment (K) and (B) were four times, whereas in (P) two times and (H) once. Difference of tank colors did not have significantly effect to larval survival rate (P>0.05), which was 4.87±3.74% (Y), 2.28±3.52% (B), 0.28±0.49% (Bc) and 0.15±0.31% (W). In contrast, the difference of tank colors had very significant effect (P <0.01) on larval total length, where the larval total length from (H) and (P) is greater than (B) and (K). Larvae from (P) had the highest number of rotifers in their digestion tract, while larvae (B) had the least number. The light intensity above the water surface of each different tank colors did not differ much. However, the light intensity reflected from water surface from (K) and (P) had higher intensity than from (B) and (H). Based on these results, tank color yellow is highly recommended to use in early stage larvae rearing of coral trout.